Analysis of Exhaust Gas Heat Utilization in Waste Heat Recovery Power Generator at Indarung V Factory PT Semen Padang - Mayang Safira; Melda Latif; Zaini Zaini; Aulia Aulia; Mumuh Muharam; Waweru Njeri (Electrical Engineering Dept, Engineering Faculty, Universitas Andalas, 2023)
Increasing energy efficiency in the cement production process at PT Semen Padang is carried out by reusing exhaust gas to produce electricity using Waste heat recovery power generation (WHRPG) with a capacity of 8.5 MW. WHRPG is a technology for utilizing exhaust gas heat as a source of heat energy to heat feed water into steam by using a suspension preheater (SP) boiler and air quenching cooler (AQC) boiler. This study aims to calculate the power potential of the steam heat influenced by the steam temperature and the mass flow rate of the steam produced by the boiler, to calculate the efficiency of the boiler using the direct method by comparing the boiler output heat against the boiler input heat, to calculate the turbine efficiency based on the difference between the steam enthalpy enter the turbine against the steam enthalpy out of the turbine and the isotropic enthalpy of the steam out of the turbine and to calculate the power generated by WHRPG at PT Semen Padang. The results obtained in this study are the total potential power of steam heat is 19.778 MW, the boiler AQC efficiency is 70.30%, the boiler SP efficiency is 94.04% and the turbine efficiency is 78.64%. The electricity generated by PT Semen Padang's WHRPG is 3.70 MW.